GLOSSARY ENGLISH MATHEMATICS: LEARNING MEDIA TO IMPROVE STUDENTS' DIGITAL AND VOCABULARY LITERACY - Septia, Tika; Fachrudin, Achmad Dhany; Kristanto, Vigih Hery (EDUPEDIA, 2024)
English is a demand in the 5.0 era, especially in education. Students use many English journals and references. However, the students' interest in English still needs to be improved. Students need to understand books in English. An English math glossary can help them understand math terms in English. The English Mathematical Glossary contains explanations of mathematical terms—development of a Mathematical English Glossary using an Android application. Android applications have recently developed rapidly because of their nature that can be used anywhere and anytime. This research is development research using the SDLC (System Development Life Cycle) model. The Mathematical English Glossary's development has undergone five stages: planning, analyzing, designing, implementing, and testing. The product developed is an Android-based Mathematical English Glossary. The study results show that the Android-based Mathematical English Glossary is valid and practical in content, language, and presentation and effectively increases student digital literacy. After the vocabulary size test was carried out, it was found that the Android-based Mathematical English Glossary could improve the vocabulary skills of mathematics education students